CACTI: Use of a survey instrument as a semistructured interview protocol to facilitate teacher retrospection on bi/multilingual practices in EMI. (October 2022) - Mendoza, Anna; Ou, Jiaen
Abstract: In this study, the researchers used a survey as a semistructured interview protocol to examine teachers' use of students' other languages in English-medium instruction (EMI) by conducting interviews with 16 primary and secondary teachers in EMI schools in Hong Kong, Guangdong, Fujian, and Zhejiang. During the two parts of the interview (Part 1: Demographic Information and Part 2: Bi/multilingual Practices), which lasted 1.5–2 h, teachers shared their pedagogical practices based on one class of primary or secondary students. Part 1 elicited teachers' geographic and institutional context, grade and subject matter, class language demographics, and teacher language knowledge, while Part 2 consisted of 30 multiple choice items representing different bi/multilingual classroom practices, categorized based on the literature into learning purposes, pedagogical or spontaneous practices, classroom language policies, and modality directions. Teachers rated the importance of each of the 30 practices on a Likert scale ("5/Very important" to "1/Not important") and gave justifications and explanations that were coded inductively. Table and interview analyses show (1) which practices stood out as the most controversial, (2) what deliberations about contextual factors were involved in decision-making about them, and (3) implications for teacher professional development.